FDI and income inequality: evidence from a panel of US states - Pandej Chintrakarn; Dierk Herzer; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2010)
This study employs state-level panel data to explore the relationship between inward foreign direct investment (FDI) and income inequality in the United States. Using panel cointegration techniques that allow for cross-sectional heterogeneity, cross-sectional dependence, and endogenous regressors, we find that the short-run effects of FDI on income inequality are insignificant or weakly significant and negative. In the long run, however, FDI exerts a significant and robust negative effect on income inequality in the United States. This result for the United States as a whole does not imply that FDI narrows income gaps in the long run in each individual state. There is considerable heterogeneity in the long-run effects of FDI on income inequality across states, with some states (21 out of 48 cases) exhibiting a positive relationship between FDI in income inequality.
Keywords: F21; D31; C23; 330; FDI; Inequality; Panel Cointegration; United States